2006
DOI: 10.1038/sj.bjc.6603285
|View full text |Cite
|
Sign up to set email alerts
|

Association of 12 serum biochemical markers of angiogenesis, tumour invasion and bone turnover with bone metastases from breast cancer: a crossectional and longitudinal evaluation

Abstract: Complex biological pathways including angiogenesis, invasion, osteoclastic activation and bone matrix degradation are involved in the formation of bone metastasis (BM). The aim of our study was to investigate the cross-sectional and longitudinal associations of a panel of 12 serum biochemical markers reflecting biological pathways underlying BM development. In a cross-sectional study, we investigated 29 patients with primary breast carcinoma without BM (BC/BMÀ), 28 patients with breast carcinoma and BM (BC/ BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 41 publications
1
40
1
Order By: Relevance
“…MMP-9 is a MMP highly expressed in osteoclasts and is likely to act as collagenolytic enzyme during bone matrix degradation (38,40). Of note, VEGF and MMP-9, together with bone resorption markers, were found to be positively correlated with bone metastases in patients with breast carcinomas (41). VEGF is known to directly enhance bone resorption and survival of mature rabbit osteoclasts (42).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 is a MMP highly expressed in osteoclasts and is likely to act as collagenolytic enzyme during bone matrix degradation (38,40). Of note, VEGF and MMP-9, together with bone resorption markers, were found to be positively correlated with bone metastases in patients with breast carcinomas (41). VEGF is known to directly enhance bone resorption and survival of mature rabbit osteoclasts (42).…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenic factors in the bone marrow are essential for the cross-talk of osteoclasts, osteoblasts, and bone marrow endothelial cells. In patients with skeletal metastases, the expression of angiogenic factors was associated with osteoclast-mediated osteolysis and, vice versa, antiangiogenic therapy resulted in antiresorptive treatment response in these lesions (1)(2)(3)(4). Recently, a close anatomic relation between capillaries and bone remodeling units consisting of osteoclasts and osteoblasts was observed in osteolytic lesions, indicating a possible interaction between angiogenesis and bone resorption (5).…”
mentioning
confidence: 99%
“…Chemotherapeutic aromatase inhibitors (e.g., exemestane and anastrozole) have been shown to directly inhibit osteoclast differentiation and bone resoption markers leading to osteoporosis in postmenopausal women with early BC [6], yet with apparently increased bone resorption biochemical markers, as also had been shown earlier [31,32]. It has been shown that osteoporotic bone loss and bone metastasis ultimately share a pathophysiologic pathway that stimulates bone resorption by increasing the formation and activity of osteoclasts [4].…”
Section: Discussionmentioning
confidence: 63%